QUALITY CONTROL ASSESSMENT OF FOUR BRANDS OF TINIDAZOLE TABLET MARKETED WITHIN KADUNA CITY, NIGERIA - A. MUNTAKA; A. MUSA; M.A.USMAN; A.Y. IDRIS; OLOWO-OKERE A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Like most drugs, various brands of tinidazole tablets are available in Nigeria and therapeutically equivalent products are being selected for various reasons. The aim of the study was to quarantine the different tablets brands that are commonly used, accessible and prescribed to see if the conform to the official standard and the specifications set by the regulatory agencies. The weakness of our regulatory agencies, rising incidence of fake and counterfeiting of drugs, increase in number of generic substitutes of tinidazole tablets in the market in addition to increase prescription and usage of tinidazole tablets in our society due to Parasitic and bacterial infections of the gastrointestinal responsible for significant morbidity and mortality worldwide with substantial increase of trichomoniasis infection among African women warrant this study. Four tablet brands of tinidazole sourced from the major pharmacies within Kaduna metropolis were identified, assayed and evaluated for uniformity of weight, friability, disintegration time, uniformity of dosage units and dissolution following standard BP procedure. The four generic brands of tinidazole were identified using their IR spectra and melting points which were found to be within the range of (125 to 128 °C) specified limits for tinidazole and passed the uniformity of weight and friability tests with the range of less than 1%. The absolute drug content of tinidazole in two of the four brands was however outside the specified range. Three of the four brands passed the disintegration tests within the disintegration time frame of less than 15 minutes. The four brands of tinidazole tablets marketed in Kaduna city vary in quality and so their use interchangeably should be carefully considered. Keywords: